Идентитетот како реинтегрирано културно наследство во „Историјата“ на Ѓорѓија Пулевски - Tasevska Hadji Boshkova, Iskra (Институт за македонска литература, 2011)
The analysis of how identity experiences constant cultural redetermination in Pulevski’s “History” implies the indispensable suppletion of existing accounts, as well as the need for reaffirmation of culturally inherited works of art, which are usually cast out in the area of non-artistic or quasi-artistic (due to the dominant central genres’ conception). Pulevski’s predetermined goal to create a Balkan history puts him into a position to search and rediscover, but also to rework historical facts and existing representations, that obviously and to great extent bear the stigma of the dominant ideologies, of the context in which they have been created. At first glance, the discourse in “History” seems completely monologic, trapped into the constant need for finding an adequate way of unmasking historical “lies”, that on the other hand acquires its implicit ideology. However, the realization of how Pulevski prefigure (and transfigure) the historical fact destroys this primal illusion. The act of envisaging the notion of national as cultural unity of differences does not diminish the incoherencies that exist in certain parts, yet it underlines the “ideological” and ”formal-argumentative” explanation in historical representation, whose ultimate achievement is not (and should not be) the creation of stereotypes, and stigmatized concepts.
Keywords: identity, historism (historicity), historic representation, Balkan history, realism in mode of synecdoche, microetimology, transfiguration of historic facts, polemic ideology